2022
DOI: 10.3390/life12081113
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Heart Disease in Patients with Inflammatory Bowel Disease: Risk Factors, Mechanisms and Prevention

Abstract: According to new research, a possible association between inflammatory bowel disease (IBD) and an increased risk of ischemic heart disease (IHD) has been demonstrated, but this concern is still debatable. The purpose of this review is to investigate the link between IHD and IBD, as well as identify further research pathways that could help develop clinical recommendations for the management of IHD risk in IBD patients. There is growing evidence suggesting that disruption of the intestinal mucosal barrier in IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Intestinal LPS binds LPS-binding protein and celiac particles, and enters the body's circulation through the lymphatics, thus enhancing the inflammatory process [46]. In addition, disruption of the intestinal mucosal barrier in UC leads to the transfer of LPS and other endotoxins into the bloodstream, thereby inducing a pro-inflammatory cytokine response that leads to endothelial dysfunction, atherosclerosis and acute cardiovascular events [14]. KEGG enrichment analysis highlighted the importance of lipid and atherosclerosis, RA, NF-kappa B, IL-17 and Tolllike receptor signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal LPS binds LPS-binding protein and celiac particles, and enters the body's circulation through the lymphatics, thus enhancing the inflammatory process [46]. In addition, disruption of the intestinal mucosal barrier in UC leads to the transfer of LPS and other endotoxins into the bloodstream, thereby inducing a pro-inflammatory cytokine response that leads to endothelial dysfunction, atherosclerosis and acute cardiovascular events [14]. KEGG enrichment analysis highlighted the importance of lipid and atherosclerosis, RA, NF-kappa B, IL-17 and Tolllike receptor signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…UC causes systemic inflammatory responses and promotes hypercoagulation in the body [13]. Furthermore, disruption of the intestinal mucosal barrier leads to the transfer of lipopolysaccharides (LPS) and other endotoxins into the bloodstream, thereby inducing the secretion of pro-inflammatory cytokines and leading to endothelial disturbances, atherosclerosis and acute cardiovascular events [14]. Gut microecological dysregulation increases plaque vulnerability by affecting lipid metabolism and the inflammatory response [15].…”
Section: Introductionmentioning
confidence: 99%
“…Frequent complications associated with disease progression in CD are abscess and stricture formation, intestinal obstruction, and fistulas [4]. Moreover, patients with IBD have a higher risk of developing other complications, such as asthma or bronchitis, psoriasis, pericarditis, ischemic heart disease, and colon carcinoma [7][8][9][10]. Several key factors are related to the development of IBD, including genetic components (over 240 nonoverlapping genetic risk loci), environmental elements (e.g., smoking, diet, drugs, geography, social stress, and psychological elements), microbial dysbiosis, and altered immune responses [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the recognized traditional cardiovascular risk factors [1,2], such as smoking, hyperlipidemia, hypertension, diabetes, etc., an increasing number of epidemiological studies have shown that chronic inflammation plays an important role in the pathogenesis of atherosclerosis (AS) and CVD. Many epidemiological studies [3][4][5] have shown that CVD has been linked to rheumatoid arthritis and systemic lupus erythematosus, however, the association between inflammatory bowel disease (IBD) and CVD remains unclear. Emerging data indicate that the change of intestinal flora in IBD leads to the release of inflammatory cytokines into systemic circulation, thus accelerating the process of AS [6,7].A recent longitudinal study of 210,162 patients with IBD showed that the 3-month periods before and after inflammatory bowel disease-related hospitalization were associated with an increased risk of acute arterial events in both Crohn's disease and ulcerative colitis [8].…”
Section: Introductionmentioning
confidence: 99%